1982
DOI: 10.1002/ajmg.1320120409
|View full text |Cite
|
Sign up to set email alerts
|

Spinal dysraphia as an autosomal dominant defect in four families

Abstract: Four families were selected randomly on the basis of the occurrence of spina-bifida cystica and/or spina bifida occulta in one or more family members. Sixty-three relatives were studied clinically and roentgenologically; their roentgenograms were evaluated blindly. Twenty-eight were clinically and roentgenologically normal; 35 were diagnosed as having spina bifida occulta (SBO), spina bifida cystica (SBC), vertebral anomalies, and/or external defects usually interpreted as evidence for SBO. Excluding one proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…Holmes et a1 [ 19761 have pointed out that NTD can be part of syndromes such as the Meckel syndrome, or can occur secondarily to amniotic bands. NTD attributable to single genes in some cases have also been described [Toriello et al, 1980;Fineman et al, 1982;Fellous et al, 19821 as well as possible heterogeneity among the nonsyndromic, "isolated" NTD [Toriello and Higgins, 19831. As a corollary to this precaution, one needs to be aware of this heterogeneity before giving recurrence risks in a genetic counseling situation.…”
Section: Toriello Et Al (This Study)mentioning
confidence: 93%
“…Holmes et a1 [ 19761 have pointed out that NTD can be part of syndromes such as the Meckel syndrome, or can occur secondarily to amniotic bands. NTD attributable to single genes in some cases have also been described [Toriello et al, 1980;Fineman et al, 1982;Fellous et al, 19821 as well as possible heterogeneity among the nonsyndromic, "isolated" NTD [Toriello and Higgins, 19831. As a corollary to this precaution, one needs to be aware of this heterogeneity before giving recurrence risks in a genetic counseling situation.…”
Section: Toriello Et Al (This Study)mentioning
confidence: 93%
“…A simple, fully penetrant autosomal recessive pattern of inheritance for NTDs is unlikely, given that the risk to siblings ranges from 2 to 5%, considerably lower than the 25% expected under strict Mendelian recessive inheritance or 50% under Mendelian dominant inheritance. Formal segregation analysis studies demonstrating evidence of a major gene have been performed in a series of NTD families, one demonstrating evidence for a major dominant gene and another for a major gene with recessive effect [18, 19]. Reports of substantial familial aggregation have been documented in anencephaly [20, 21]and other broad-spectrum NTD phenotypes, such as sacral detects with anterior meningocele [22]and sacral agenesis [23].…”
Section: What Causes Ntds?mentioning
confidence: 99%
“…Say et al fi reported a family in whom two males were stillborn with severe malformations, suggesting that the hemizygous state in the male could be lethal. Fineman et al 2 described four families with spinal dysraphia and proposed an autosomal dominant inheritance. This same pattern of inheritance was observed by Yates et al 8 who reported a family in whom at least 11 individuals of three generations had partial sacral agenesis and have had either anterior sacral meningoceles, teratomas or both.…”
Section: Commentsmentioning
confidence: 99%